THE ASSOCIATION OF INTERLEUKIN-6 AND PROCALCITONIN LEVELS WITH CLINICAL OUTCOME OF COVID-19 DISEASE - Ramadhani, Renata Evelyn; Solikhah, Amanatus; Ariani, Rizka (Biomedika, 2025)
Severe and potentially fatal complications can arise from COVID-19, especially when the immune system triggers an exaggerated inflammatory reaction. This study examines the possible relationship between serum levels of Interleukin-6, Procalcitonin and clinical outcomes in hospitalized COVID-19 patients. Using a retrospective cross-sectional design, this study evaluated data from 71 patients hospitalized at RSUD Wates in 2021. Biomarker level differences between survivors and non-survivors were assessed using the Mann-Whitney U test and binary logistic regression. IL-6 concentrations were significantly higher in non-surviving patients and continued to serve as an independent predictor of mortality after adjustment. Conversely, while PCT levels were higher in non-survivors, they did not retain independent prognostic significance in multivariate analysis. IL-6 is crucial in forecasting severe outcomes, likely because of its role in cytokine storms and immune dysregulation. Initial IL-6 measurement may help detect patients at higher risk and support decisions regarding intensive care. Meanwhile, raised PCT levels require careful interpretation within the broader clinical picture. Additional research involving larger sample sizes and robust methodologies is required to determine the value of combined biomarkers in COVID-19 risk evaluation.